2010
DOI: 10.1027/0227-5910/a000027
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Patient Suicide on the Professional Reactions and Practices of Mental Health Caregivers and Social Workers

Abstract: Beyond the emotional and professional impact, patient suicide may have also a formative influence, encouraging professionals to review and improve their working practices. Recommendations to help mental health and social professionals who have experienced a patient suicide are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…5,31 A recent study on the impact of patient suicide on mental health professionals showed that effects on emotional and cognitive areas and on clinical practice diminish over time. 13 The temporal-emotional pattern described above overlaps with the typical grief process following a loss, which is initially characterized by psychological pain, guilt, anger, and feelings of betrayal; and then subsequently by frustration and helplessness; and finally by reassurance. This means that patient suicidal behavior, be it attempted or completed, is an emotionally significant event for the therapist as it is for the relatives of the patient.…”
Section: Attempted Suicidementioning
confidence: 92%
See 3 more Smart Citations
“…5,31 A recent study on the impact of patient suicide on mental health professionals showed that effects on emotional and cognitive areas and on clinical practice diminish over time. 13 The temporal-emotional pattern described above overlaps with the typical grief process following a loss, which is initially characterized by psychological pain, guilt, anger, and feelings of betrayal; and then subsequently by frustration and helplessness; and finally by reassurance. This means that patient suicidal behavior, be it attempted or completed, is an emotionally significant event for the therapist as it is for the relatives of the patient.…”
Section: Attempted Suicidementioning
confidence: 92%
“…13 It has been reported that, following a completed suicide, many psychiatrists experience significant concerns about patients with a history of suicidal behavior; some may even refuse to treat other suicidal patients, and most are significantly concerned that another patient may become suicidal. 11,12 This is not consistent with the results of our study; rather, we found that the attempted suicide did not affect the psychiatrists' professional attitude at all in 66% of the cases.…”
Section: Attempted Suicidementioning
confidence: 99%
See 2 more Smart Citations
“…One in five of those who die by suicide had some contact with mental health services in the month prior to their death (Stene‐Larsen & Reneflot, ). Most mental health professionals encounter suicidal behaviour during their career (Hendin, Haas, Maltsberger, Szanto, & Rabinowicz, ), and some even experience a patient's suicide (Gulfi, Dransart, Heeb, & Gutjahr, ). Different methods of therapy, such as cognitive–behavioural therapy, problem‐solving therapy, and interpersonal psychotherapy, have been proved to be effective in treating suicide and reducing suicidal behaviour, ideation, and suicide attempts.…”
Section: Introductionmentioning
confidence: 99%